Developing stakeholder-driven scenarios on land sharing and land sparing – Insights from five European case studies. (1st July 2019) - Karner, Katrin; Cord, Anna F.; Hagemann, Nina; Hernandez-Mora, Nuria; Holzkämper, Annelie; Jeangros, Bernard; Lienhoop, Nele; Nitsch, Heike; Rivas, David; Schmid, Erwin; Schulp, Catharina J.E.; Strauch, Michael; et al.
Abstract: Empirical research on land sharing and land sparing has been criticized because preferences of local stakeholders, socio-economic aspects, a bundle of ecosystem services and the local context were only rarely integrated. Using storylines and scenarios is a common approach to include land use drivers and local contexts or to cope with the uncertainties of future developments. The objective of the presented research is to develop comparable participatory regional land use scenarios for the year 2030 reflecting land sharing, land sparing and more intermediate developments across five different European landscapes (Austria, Germany, Switzerland, The Netherlands and Spain). In order to ensure methodological consistency among the five case studies, a hierarchical multi-scale scenario approach was developed, which consisted of i) the selection of a common global storyline to frame a common sphere of uncertainty for all case studies, ii) the definition of three contrasting qualitative European storylines (representing developments for land sharing, land sparing and a balanced storyline), and iii) the development of three explorative case study-specific land use scenarios with regional stakeholders in workshops. Land use transition rules defined by stakeholders were used to generate three different spatially-explicit scenarios for each case study by means of high-resolution land use maps. All scenarios incorporated various aspects of land use and management to allow subsequent quantification of multiple ecosystem services and biodiversity indicators. The comparison of the final scenarios showed both common as well as diverging trends among the case studies. For instance, stakeholders identified further possibilities to intensify land management in all case studies in the land sparing scenario. In addition, in most case studies stakeholders agreed on the most preferred scenario, i.e. either land sharing or balanced, and the most likely one, i.e. balanced. However, they expressed some skepticism regarding the general plausibility of land sparing in a European context. It can be concluded that stakeholder perceptions and the local context can be integrated in land sharing and land sparing contexts subject to particular process design principles. Highlights: Hierarchical scenario approach to integrate multi-scale drivers and local context. Quantitative scenarios suitable for ecosystem service and biodiversity assessment. Scenarios implement land sharing and land sparing strategies in European regions. Results are standardized, comparable case study-specific land use scenarios.